VIRTUAL REALITY TECHNOLOGY RESEARCH FOR MENTAL HEALTH SUPPORT - ANDRUNYK, VASYL; KRYVOSHYYA, MAKSYM (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Over the last decade, extended technologies (Extended Reality) have reached maximum popularity in almost all spheres of human activity, for example in education, medicine, industrial production, etc. Due to the fact that virtual and augmented reality devices are becoming more and more affordable, there is an increasing variety of software that allows their use by pupils and students, persons with special needs and specialists of various industries. In particular, virtual reality provides an opportunity to immerse yourself in pre-designed and safe 3D environments, which makes it possible to feel full presence, experiencing new emotions and impressions. This makes it possible to use virtual reality technologies for psychotherapists who conduct therapy and treatment of various mental illnesses – phobias, post-traumatic stress disorders, depression, etc.The paper examines the expediency of using augmented reality technologies (namely, virtual reality) for the prevention of mental health for people with mental health problems. It is indicated that information technologies based on virtual reality are very promising for mental health support. An analysis of current scientific works was carried out, which confirm the effectiveness of using virtual reality to overcome various phobias and post-traumatic stress, stress prevention and depression.A diagram of options for using the functioning of the developed mental health support system with the use of virtual reality scenes is given. The work also describes the current implementation of a virtual reality scenario for the prevention of mental health problems, developed in the environment of the Unreal Engine 5.x game engine. It is noted that an autonomous Meta Quest 2 VR helmet was used to reproduce the pre-thought-out scenario.
Keywords: virtual reality; mental health; disorders; stress; game engine; Unreal Engine